Summer variability of the atmospheric NO2 : NO ratio at Dome C on the East Antarctic Plateau - A. Barbero; R. Grilli; M. M. Frey; C. Blouzon; C. Blouzon; D. Helmig; N. Caillon; J. Savarino (Atmospheric Chemistry and Physics, 2022)
Previous Antarctic summer campaigns have shown unexpectedly high levels of oxidants in the lower atmosphere of the continental plateau and at coastal regions, with atmospheric hydroxyl radical (OH) concentrations up to 4 × 106 cm−3. Such high reactivity in the summer Antarctic boundary layer results in part from the emissions of nitrogen oxides (NOx ≡ NO + NO2) produced during photo-denitrification of the snowpack, but its underlying mechanisms are not yet fully understood, as some of the chemical species involved (NO2, in particular) have not yet been measured directly and accurately. To overcome this crucial lack of information, newly developed optical instruments based on absorption spectroscopy (incoherent broadband cavity-enhanced absorption spectroscopy, IBBCEAS) were deployed for the first time at Dome C (−75.10 lat., 123.33 long., 3233 m a.s.l.) during the 2019–2020 summer campaign to investigate snow–air–radiation interaction. These instruments directly measure NO2 with a detection limit of 30 pptv (parts per trillion by volume or 10−12 mol mol−1) (3σ). We performed two sets of measurements in December 2019 (4 to 9) and January 2020 (16 to 25) to capture the early and late photolytic season, respectively. Late in the season, the daily averaged NO2:NO​​​​​​​ ratio of 0.4 ± 0.4 matches that expected for photochemical equilibrium through Leighton's extended relationship involving ROx (0.6 ± 0.3). In December, however, we observed a daily averaged NO2:NO ratio of 1.3 ± 1.1, which is approximately twice the daily ratio of 0.7 ± 0.4 calculated for the Leighton equilibrium. This suggests that more NO2 is produced from the snowpack early in the photolytic season (4 to 9 December), possibly due to stronger UV irradiance caused by a smaller solar zenith angle near the solstice. Such a high sensitivity of the NO2:NO ratio to the sun's position is of importance for consideration in atmospheric chemistry models.